Integrating Reading Lesson Into Speaking Practice Through Jigsaw Technique (A classroom research in Bina Sarana Informatika University) - Mentari Pratami; Erniyanti Nur Fatahhela Dewi (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2024)
To have an effective learning and teaching English, it should cover four language skills such as listening, speaking reading, and writing. It is shown in practice, that the process of teaching involved some language skills i.e when teaching listening will involve speaking and reading. And when teaching speaking will include listening and reading, the same case when teaching reading will contain speaking and listening. Though the main purpose of teaching reading is to develop knowledge and get information, but speaking practice could be placed in. Through jigsaw reading technique, it is a good idea then to integrate the reading activities into speaking practice. Therefore, this technique is applied to students of Bina Sarana Informatika University. The purpose of this research is to know if teaching reading will also result speaking skill. The research was carried out from October 2023 to January 2024. This an action research that applied six (6) stages in presenting jigsaw reading. They include; 1). Preparation, 2). Expert group, 3). Presentation group, 4). Debriefing, 5). Group processing, and 6). Individual accountability. The action research employs twenty (20) students of semester 3 Bina Sarana Informatika University. The result shows that most students gained good speaking skill. This conclusion is made based on the presentation speaking test result which the grade of “the accuracy & fluency” aspect was range from good to excellent score. The number of this scores reached to 18 (90%) out of 20 students. The result showed that students who got fair score is only 2 (10%). After learning and discussing the content of the paragraph most students can answer the questions orally. The students who got good score on “Content Mastery “ is 12 students (60%), and the aspect of “answering questions” is 18 students (90%) got good scores. Since the main subject is reading, therefore the researcher also evaluated the result of the reading comprehension test. Based on the test result most students can do the test well. This is shown with the average score is 87. Therefore, it is concluded that integrating reading lesson into speaking practice through jigsaw technique is effective and applicable for students of university. The process also created togetherness among the students. Jigsaw technique also stimulated students to read intensively. By doing such activity that students speaking ability is improved